The book of three. - Alexander, Lloyd (Alexander, Lloyd. Chronicles of Prydain., 1964)
A fairy tale with origins in Welsh mythology, about the imaginary kingdom of Prydain. In this fantasy Toran, Assistant Pig-Keeper, has many adventures on a harzardous mission to save Prydain from the forces of evil.